2011
DOI: 10.1111/j.1365-2869.2010.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep efficiency during sleep studies: results of a prospective study comparing home-based and in-hospital polysomnography

Abstract: , the clinical use of unattended home-based polysomnography (PSG) is not recommended. To assess whether sleep efficiency is better at home, we have performed a prospective, crossover, single-blind study comparing unattended home-versus attended in-hospital PSG in a population referred for high clinical suspicion of obstructive sleep apnoea syndrome (OSA). Within 2 weeks, all the patients underwent both PSG performed by the same sleep technician, which were analysed by another blinded technician. Payments for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 21 publications
5
71
1
1
Order By: Relevance
“…The unattended level 1 studies had similar rates of technical failures, despite using full polysomnography equipment, suggesting the failures were because a sleep technician was not in attendance. 106 Despite the heterogeneity we saw at some apnea-hypopnea index cut-offs in our metaanalysis, the pooled estimates of diagnostic accuracy parameters appear reliable. We used a model that accounts for this heterogeneity [107][108][109][110] despite the use of different level 3 devices, which each measured the same core parameters.…”
Section: Discussionmentioning
confidence: 67%
“…The unattended level 1 studies had similar rates of technical failures, despite using full polysomnography equipment, suggesting the failures were because a sleep technician was not in attendance. 106 Despite the heterogeneity we saw at some apnea-hypopnea index cut-offs in our metaanalysis, the pooled estimates of diagnostic accuracy parameters appear reliable. We used a model that accounts for this heterogeneity [107][108][109][110] despite the use of different level 3 devices, which each measured the same core parameters.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, Jaye et al [18 ]reported no difference between iVAPS and pressure support ventilation in restrictive patients. However, all of these studies focused only on sleep quality measured in hospital via PSG [7,8,18], and it is widely accepted that sleep quality at home is different from that in hospital [22]. Data about how NPPV using target volumes influences sleep quality at home and whether there might be an improvement in sleep quality over time are lacking; we assessed these in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, better patient acceptability and preference for home monitoring have been reported [25] . Portier et al [26] reported longer sleep duration at home than in the laboratory and Bruyneel et al [23] found better sleep efficiency at home.…”
Section: Advantages and Limitations Of Bismentioning
confidence: 99%
“…Certain authors have suggested that this can be achieved with clinical assessment, measurement of arterial blood gas and nocturnal SpO 2 under NIV [21] , although others recommend using PG or PSG as the gold standard [22,23] . Some home ventilators include built-in monitoring systems allowing the clinician to assess various PG parameters.…”
Section: Clinical Significancementioning
confidence: 99%